Expression of a Lychee PHOSPHATIDYLCHOLINE:DIACYLGLYCEROL CHOLINEPHOSPHOTRANSFERASE with an Escherichia coli CYCLOPROPANE SYNTHASE Enhances Cyclopropane Fatty Acid Accumulation in Camelina Seeds. Issue 3 (13th May 2019) - Yu, Xiao-Hong; Cai, Yuanheng; Chai, Jin; Schwender, Jorg; Shanklin, John
Abstract : Lychee accumulates ∼40% cyclopropane fatty acid in seed, and heterologous co-expression of its phosphatidylcholine diacylglycerol cholinephosphotransferase with E. coli cyclopropane synthase in camelina seed enhances cyclopropane fatty acid accumulation. Abstract: Cyclopropane fatty acids (CPAs) are useful feedstocks for biofuels and bioproducts such as lubricants and biodiesel. Our goal is to identify factors that can facilitate the accumulation of CPA in seed triacylglycerol (TAG) storage oil. We hypothesized that the poor metabolism of CPA through the TAG biosynthetic network could be overcome by the addition of enzymes from species that naturally accumulate CPA in their seed oil, such as lychee ( Litchi chinensis ), which contains approximately 40% CPA in TAG. Our previous work on engineering CPA accumulation in crop and model plants identified a metabolic bottleneck between phosphatidylcholine (PC), the site of CPA biosynthesis, diacylglycerol (DAG), and TAG. Here, we report the cloning and heterologous expression in camelina ( Camelina sativa ) of a lychee PHOSPHATIDYLCHOLINE:DIACYLGLYCEROL CHOLINEPHOSPHOTRANSFERASE ( PDCT ), which encodes the enzyme that catalyzes the transfer of the phosphocholine headgroup from PC to DAG. Camelina lines coexpressing LcPDCT and Escherichia coli CYCLOPROPANE SYNTHASE ( EcCPS ) showed up to a 50% increase of CPA in mature seed, relative to the EcCPS background. Stereospecific lipid compositional analysis showed that the expression of LcPDCT strongly reduced the level of C18:1 substrate at PC- sn- 1 and PC- sn -2 (i.e. the sites of CPA synthesis), while the levels of CPA increased in PC- sn- 2, DAG- sn- 1 and DAG- sn -2, and both sn -1/3 and sn -2 positions in TAG. Taken together, these data suggest that the addition of PDCT facilitates more efficient movement of CPA from PC to DAG and establishes LcPDCT as a useful factor to combine with others to enhance CPA accumulation in plant seed oil.